The feasibility of day case laparoscopic cholecystectomy in a single hepatobiliary centre, Hospital Sultanah Bahiyah from January 2008 to December 2010 - Bob, Lee Say (2013)
The development of day case laparoscopic cholecystectomy (DCLC) has been catalyzed by the drive to achieve cost-effectiveness and shortened waiting time for operation. Nevertheless, the DCLC in Malaysia is still uncommon and limited. The aims of this study were to determine the feasibility of DCLC in a single hepatobiliary centre, to determine the success rate of DCLC, to identify reasons for unplanned admission and to establish predictive factors of failure in DCLC. This was a retrospective review of 91 patients who underwent DCLC between January 2008 to December 2010. Information on these patients were retrieved and analysed for the reasons of unplanned admission and predictive factors of failure in DCLC. Statistical analyses were performed using SPSS version 19.0. There were 70 females and 21 males with mean ± SD ages were 37.16 ± 10.28 and 44.62 ± 12.03 respectively. Ninety six percent of the patients were ASA class I and 93% of patients had no comorbidities. Ninety one percent of cases were performed by hepatobiliary trainees with median operating time for them was 51.0 min IQR 18, and 45.0 min IQR 73 for consultant (P= 0.569). Seventy four percent of patients were successfully discharged following DCLC. There was no readmission following successful discharge from DCLC. The most common reason for admission was conversion to open surgery (7.7%). The predictive factors for failure of DCLC were length of operation [adjusted OR 1.04 (1.01, 1.07)] and severity of adhesion [adjusted OR 38.42 (3.18, 464.84)]. Patient selection is of paramount importance in the success of DCLC. This study has showed that DCLC is feasible in selected hospital with hepatobiliary unit in Malaysia.